(NtIPOLOGI^ESKIE ASPEKTY FONETI^ESKIH IZMENENIJ W PRASLAWQNSKOM (B:s (NdOKLADY (B/s - (N~EKMAN(B, (NwALERIJ nIKOLAEWI^s; (NbELORUSSKIJ KOMITET SLAWISTOW an bssrs; (NmEVDUNARODNYJ S_EZD SLAWISTOWs 1978 : (NmINSK(B)s ((NmINSK (B:s (NnAUKA I TEHNIKA(B,s, 1978)
(NrEZ@ME S(B.: 42 (NNA ANGL(B. (NQZ(B.s
(NbIBLIOGR(B. (NW PODSTRO^(B. (NPRIME^(B. (NNA RUS(B. (NI ANGL(B. (NQZ(B.s
Keywords: (NrUSSKIJ QZYKs; (NpRASLAWQNSKIJ QZYK (B- (NfONETIKAs